Knowledge Management Strategies to Improve Learning and Growth in Creative Industries: A Framework Model - Alexandra Sinta Wahjudewanti; Jann Hidajat Tjakraatmaja; Yudo Anggoro (Budapest International Research and Critics University, 2021)
The aim of this study is to propose a framework model to capture the knowledge management (KM) process and KM enablers and their connection to improving learning and growth in creative industries. This study is a literature review that analyses several articles related to KM and creative industries. Field observations were conducted at two creative industries to verify the literature review results. This review explores several studies of KM enablers and KM processes to identify KM’s relationship with organizational performance. Organizational performance can be measured from several perspectives, one of which is the tangible perspective of learning and growth. The framework model comprises three interrelated concepts of KM and performance: KM enablers, KM processes, and learning and growth as an intangible type of performance. Further study is needed to identify the types of KM enablers and KM processes to obtain a better understanding of how to improve the performance of creative industries. This study is limited to knowledge management in creative industries. Studies of KM strategies in creative industries are limited, including in Indonesia. Previous studies identify the relationship between KM implementation and improving tangible performance measurements, such as financial and customer performance. This study contributes to our knowledge of implementing KM to improve intangible performance in creative industries.